Functional Electrical Stimulation Plus Visual Feedback Balance Training for Standing Balance Performance Among Individuals With Incomplete Spinal Cord Injury: A Case Series - Houston, David J.; Lee, Jae W.; Unger, Janelle; Masani, Kei; Musselman, Kristin E. (Frontiers in Neurology, 2020)
Individuals with an incomplete spinal cord injury (iSCI) are highly susceptible to falls during walking or standing. Our objective was to evaluate a therapeutic tool for standing balance that combined functional electrical stimulation, applied bilaterally to the plantarflexors and dorsiflexors, with visual feedback balance training (FES+VFBT). Five adults with iSCI completed 12 FES+VFBT sessions over four weeks. During the training sessions, participants completed each of the four balance exercises twice. Visual feedback of the centre-of-pressure (COP) location was provided as participants completed the balance exercises and received FES to assist with performance of the exercises. A closed-loop FES system was used in which the COP was continually monitored and the level of electrical current administered was automatically adjusted. Balance abilities were assessed pre- and post- training using clinical balance scales (i.e. Berg Balance Scale, Mini-Balance Evaluation Systems Test, and Activities-specific Balance Confidence Scale) and biomechanical assessments (i.e. postural sway measures and limits of stability test during standing). User acceptability was explored through semi-structured interviews. Improvements were seen for four of the five participants on at least one of the clinical scales following completion of the training intervention. All participants showed greater maximal COP excursion area during the limits of stability test after the training intervention, whereas only one participant demonstrated a reduction in postural sway. Specific components of FES+VFBT, including the ability to safely practice challenging balance exercises, were deemed important by the participants. These results suggest that FES+VFBT has potential as an intervention for standing balance after iSCI.